Analisis faktor eksternal yang dipertimbangkan masyarakat muslim pesisir Tuban untuk mengunakan layanan Bank Thithil - Syaifudin, Ahmad; Ekawaty, Marlina (Fakultas Ekonomi, UIN Maliki Malang, 2019)
Bank Thithil is an informal financial institution that offers high-interest loan services to the public. This study aims to determine the external factors considered by coastal Muslim society to use bank thithil financial services. The data were collected through survey with questionnaires and in-depth interviews with bank thithil customers at Bulu Meduro village, Tuban regency and analyzed by exploratory factor analysis methods. The results show that there are eight external factors that are considered by customers to use bank thithil services, namely: loan compensation and accessibility factors, customer parity and service, transaction time flexibility, ease of administration, brand image, location excellence, member advantage, and limited institutional coverage syariah finance. From the results of external factor analysis, then analyzed in depth using interviews with several customers, it was found that there were two factors that became a strong drawer for Muslim society to use bank thithil services, namely the prime service factor of bank thithil and barriers of syariahÂ financial institutions.